Effects of greywater organomineral liquid fertilizer on the growth, yield performance, and proximate composition of chili (Capsicum annum L.) - Si, Li Tan; Kasim, Susilawati; Mohammad Yusoff, Martini; Zaibon, Syaharudin; Raguraj, Sriharan (Universiti Putra Malaysia, 2023)
The production cost of chili in the fertigation system has increased recently due to the high cost of water-soluble fertilizers used in the system. Laundry greywater and biodegradable vegetable waste are rich in nutrients essential for plant growth. Thus, this research aims to investigate the effects of greywater organomineral fertilizer (OMF) on the chili plants’ growth and yield performance in the fertigation system. The experiment was laid out in a completely randomized design under the rain shelter. OMF produced from laundry water and vegetable waste was applied with chemical fertilizer (CF) in different ratios, including 100% CF (T1, control), 75% CF + 25% OMF (T2), 50% CF + 50% OMF (T3), 25% CF + 75% OMF (T4), and 100% OMF (T5). Results showed that the combined use of CF and OMF produced non-significantly different chili plants from those solely treated by CF. Interestingly, chili plants treated with 50% CF and 50% OMF increased the yield by 4.71% compared to CF. Chili plants treated with 25% and 50% OMF showed non-significantly different plant height, stem diameter, plant dry weight, fruit number, and proximate composition of fruits over those treated with 100% CF. Solely application of OMF produced similar chili as CF in terms of fruit quality. The present study shows that plant performance and yield of chili were improved after the application of CF and OMF at a ratio of 50:50. It can be concluded that OMF has the potential to be used as an alternative for replacing 50% of chemical fertilizer in chili fertigation system without affecting its growth and yield.